2009
DOI: 10.1038/msb.2009.20
|View full text |Cite
|
Sign up to set email alerts
|

Glucose regulates transcription in yeast through a network of signaling pathways

Abstract: Correction to: Molecular Systems Biology 5 :245. doi:10.1038/msb.2009.2; published online 17 February 2009

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 0 publications
2
71
0
Order By: Relevance
“…From a 2-liter culture of strain Y2864 (Zaman et al, 2009) grown at 30°in SC ϩ 3% glycerol to 2-3 ϫ 10 6 cells/ml (A 660 ϭ 0.2-0.3), we removed and cross-linked (see below) 650 ml of culture as the zero time point and added glucose to 2% to the remaining culture. We then removed 650 ml of culture after 20 and 60 min and crosslinked cells by addition of formaldehyde to a concentration of 4% and incubation at room temperature for 30 min with gentle shaking; we found that spheroplasts from glycerol-grown cells are extremely fragile, necessitating increased cross-linking relative to previously published protocols.…”
Section: Nucleosomal Dna Isolationmentioning
confidence: 99%
See 4 more Smart Citations
“…From a 2-liter culture of strain Y2864 (Zaman et al, 2009) grown at 30°in SC ϩ 3% glycerol to 2-3 ϫ 10 6 cells/ml (A 660 ϭ 0.2-0.3), we removed and cross-linked (see below) 650 ml of culture as the zero time point and added glucose to 2% to the remaining culture. We then removed 650 ml of culture after 20 and 60 min and crosslinked cells by addition of formaldehyde to a concentration of 4% and incubation at room temperature for 30 min with gentle shaking; we found that spheroplasts from glycerol-grown cells are extremely fragile, necessitating increased cross-linking relative to previously published protocols.…”
Section: Nucleosomal Dna Isolationmentioning
confidence: 99%
“…This carbon source upshift significantly alters expression of more than half of all yeast genes (Wang et al, 2004;Zaman et al, 2009) and thereby provides numerous individual examples to examine the relationship between nucleosome positioning and gene expression. To perform this analysis, samples of glycerol grown cells were collected and formaldehyde cross-linked both before glucose addition and 20 and 60 min after addition.…”
Section: Genome-wide Positions Of Nucleosomes In Saccharomycesmentioning
confidence: 99%
See 3 more Smart Citations